Stress-Related Noradrenergic Activity Prompts Large-Scale Neural Network Reconfiguration - Hermans, Erno J.; van Marle, Hein J. F.; Ossewaarde, Lindsey; Henckens, Marloes J. A. G.; Qin, Shaozheng; van Kesteren, Marlieke T. R.; Schoots, Vincent C.; Cousijn, Helena; Rijpkema, Mark; Oostenveld, Robert; Fernández, Guillén (Science (American Association for the Advancement of Science), 2011)
Acute stress shifts the brain into a state that fosters rapid defense mechanisms. Stress-related neuromodulators are thought to trigger this change by altering properties of large-scale neural populations throughout the brain. We investigated this brain-state shift in humans. During exposure to a fear-related acute stressor, responsiveness and interconnectivity within a network including cortical (frontoinsular, dorsal anterior cingulate, inferotemporal, and temporoparietal) and subcortical (amygdala, thalamus, hypothalamus, and midbrain) regions increased as a function of stress response magnitudes, β-adrenergic receptor blockade, but not cortisol synthesis inhibition, diminished this increase. Thus, our findings reveal that noradrenergic activation during acute stress results in prolonged coupling within a distributed network that integrates information exchange between regions involved in autonomic-neuroendocrine control and vigilant attentional reorienting.